5(2x-7)+4=6

Simple and best practice solution for 5(2x-7)+4=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x-7)+4=6 equation:


Simplifying
5(2x + -7) + 4 = 6

Reorder the terms:
5(-7 + 2x) + 4 = 6
(-7 * 5 + 2x * 5) + 4 = 6
(-35 + 10x) + 4 = 6

Reorder the terms:
-35 + 4 + 10x = 6

Combine like terms: -35 + 4 = -31
-31 + 10x = 6

Solving
-31 + 10x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '31' to each side of the equation.
-31 + 31 + 10x = 6 + 31

Combine like terms: -31 + 31 = 0
0 + 10x = 6 + 31
10x = 6 + 31

Combine like terms: 6 + 31 = 37
10x = 37

Divide each side by '10'.
x = 3.7

Simplifying
x = 3.7

See similar equations:

| 5+4k= | | s*6+29=167 | | 7.42x+100=55.0564+10x | | -3.1+4.3=-1.9+3.7 | | 3w+7=2(w+4) | | B=4/3(j-98) | | a/12=10 | | 2x=8/3=10 | | 3x+x-x*x*645x=3 | | 5x+6=6x+7 | | 144y^2-8=27 | | 3/2×4/9 | | 4y=12-6x | | 1.027+x=3 | | (3x-1)(x-8)=0 | | 7/8x-7/8=8 | | 3x+5=6x+32 | | 37=9x+17 | | 48.944+x^2=50 | | 2(6x-8)=11x-12 | | 7(8-8b)-4=7b-11 | | p(x)=7x^3+5x^2-7x | | d^2+26d=37 | | 9x^2-125=0 | | 32x+10=42 | | 46x-63-25x=-146 | | 21/n=36/15 | | 20-15p=35 | | 81+X^2=50 | | 4x*4x-12x= | | 6w+3= | | 3x+-9=-57-8x |

Equations solver categories